Induction of the acrosomal reaction in mouse spermatozoa by the solution of pellucid zone from alpaca (Lama pacos L.) - Guzmán, Luis (2006)
Acrosin is one of the principal components in the acrosome, has trypsin-like activity and is secreted after the Acrosome Reaction (RA). The aim of this study was to study the induction of the acrosomal reaction in mouse sperms with homologous- Pellucid Zone and heterologous- Pellucid Zone. Mouse sperms were capacitated by two hours in IVF medium, supplemented with albumin, heparin and synthetic serum to 37 °C and 5% CO2 , and before they were incubated in absence of ZP and in present of solubilized ZP from mouse (0,78 mg/ml) and alpaca (0,78 mg/ml y 2,35 mg/ml). The RA was evaluated through immunocytochemistry with monoclonal antibodies anti-human acrosin C5F10 within intervals of 1 hour during four hours. The results show a signiﬁ cant increase (p<0,05) in acrosome reaction induced with homologous-ZP and heterologous-ZP.